A computational investigation of thermal effect on lithium dendrite growth. (1st April 2018) - Yan, H.H.; Bie, Y.H.; Cui, X.Y.; Xiong, G.P.; Chen, L.
Highlights: An integrated temperature-dependent phase-field Li-dendrite model is presented. The presented model is validated by using the published experimental data. The effects of temperature on the shape and size of the dendrites are investigated. The effects of the ambient temperature on dendritic morphologies are discussed. The influence of the internal heat on Li dendrites is discussed in detail. Abstract: This paper aims to computationally investigate the thermal effect, combining the internal heat and the ambient temperature, on the lithium (Li) dendrite growth process. To achieve this, the recently developed phase-field Li-dendrite model is further extended by coupling with a heat transfer model. The two models are linked via a temperature-dependent ion diffusion coefficient to investigate the evolution of the morphology and size of dendrites. Three levels of cases are used to progressively investigate the thermal effect on Li dendrites: (1) uniform ambient temperature, (2) temperature gradient along the charging direction, and (3) internal heat-induced spatially distributed temperature. The results show that the normalized dendrite length decreases as the ambient temperature increases, which agrees well with the published experimental measurements. The temperature gradient is applied in the 2-D system showing that the formation of lateral branches can be prevented with the presence of the temperature gradient. The third case shows that the temperature significantly increases at the dendrite-electrolyte interface, and the dendrite deviates from the tree-type shape to a nearly rhombic shape. The simulation results provide valuable bases for the future comprehensive studies of the temperature-dependent Li dendrite growth process.